Political Advertising Camouflage As News - Camelia Catharina Pasandaran (Ikatan Sarjana Komunikasi Indonesia, 2018)
Advanced technology has significantly influenced media and its environment, including their audience and advertisers. The changes have forced the media to rethink their business model. Native advertising, undisruptive advertising that looks like the original content of the media, is one of the new advertising form developed in the past few years. This trends started in Indonesian in 2014 as some big online media offers the native advertising space to the advertisers. In the perspective of Baudrillard’s postmodern view, this is a kind of simulation which may lead to the death of the reality. This study seeks to find the way news simulation work in Indonesian online media advertising. The result shows that the packaging, the placement, and the minimum disclosure of political native advertising have blurred the separation between commercial and editorial content. Analyzing from Baudrillard’s perspective, this news simulation is at the second stage of simulation, or evil appearance, in which people can no longer differentiate between the real news and the ads which simulate the news.